Background: Diarrhea is still a major health problem for children under five in Indonesia and is also the most common health problem for toddlers. The prevalence of diarrhea in children under five (based on the diagnosis of health workers) is 11% with a - Sari, Devi Ratna; Andoko, Andoko; Setiawati, Setiawati (Universitas Malahayati Bandar Lampung, 2023)
Background: Diarrhea is still a major health problem for children under five in Indonesia and is also the most common health problem for toddlers. The prevalence of diarrhea in children under five (based on the diagnosis of health workers) is 11% with a disparity between provinces between 5.1% (Riau Islands) and 14.2% (North Sumatra), while Lampung Province ranks 13th with a percentage of 8.8%.Purpose: To find out the relationship between mother's knowledge and emergency handling of children under five with diarrhea in the Long Health Center in Bandar Lampung City in 2022.Methods: This type of research uses quantitative, analytical survey research design with a cross sectional approach. The population and sample are mothers who have children aged under five in the Long Health Center Work Area, the sampling technique uses purposive sampling. Data analysis using univariate and bivariate using chi square.Results : Most of the knowledge of mothers about handling diarrhea as many as 121 respondents (58.7%) with poor knowledge. Most of the handling of diarrhea as many as 116 respondents (56.3%) handled diarrhea inappropriately. Conclusion: The results of the chi-square test obtained a p-value of 0.000 (≤0.05), which means that there is a relationship between mother's knowledge and emergency handling of children under five who experience diarrhea in the Panjang City Health Center Work Area, Bandar Lampung in 2022.Suggestion Further research needs to be carried out with different numbers and methods, as well as being able to examine other factors that influence the incidence of diarrhea, namely beliefs and traditions and it is hoped that this research will serve as a comparison material for future researchers. Keywords : Knowledge, Emergency Management, Diarrhea ABSTRAK Pendahuluan: Penyakit diare masih menjadi masalah kesehatan utama pada balita di Indonesia dan juga merupakan masalah kesehatan paling banyak terjadi pada balita. Prevalensi diare pada balita (berdasarkan diagnosis tenaga Kesehatan) sebesar 11% dengan disparitas antar provinsi antara 5,1% (Kepulauan Riau) dan 14,2% (Sumatera Utara), sedangkan untuk Provinsi Lampung dengan urutan ke 13 dengan persentase 8,8%Tujuan: Untuk mengetahui hubungan pengetahuan ibu dan penanganan kegawadaruratan pada anak balita yang mengalami diare di Wilayah Kerja Puskesmas Panjang Kota Bandar Lampung Tahun 2022.Metode: Jenis penelitian menggunakan kuantitatif, rancangan penelitian survey analitik dengan pendekatan cross sectional. Populasi dan sampel adalah ibu yang memiliki anak usia balita di Wilayah Kerja Puskesmas Panjang, teknik sampling menggunakan purposive sampling. Analisa data menggunakan univariat dan bivariat menggunakan chi square.Hasil : Sebagian besar pengetahuan ibu tentang penanganan diare sebanyak 121 responden (58,7%) dengan pengetahuan kurang baik. Sebagian besar penanganan diare sebanyak 116 responden (56,3%) melakukan penanganan diare secara tidak tepat.Simpulan: Hasil uji chi square didapat nilai p-value 0,000 (≤0,05) yang artinya ada hubungan pengetahuan ibu dan penanganan kegawadaruratan pada anak balita yang mengalami diare di Wilayah Kerja Puskesmas Panjang Kota Bandar Lampung Tahun 2022.Saran Perlu dilakukan penelitian lebih lanjut dengan jumlah dan metode yang berbeda, serta dapat meneliti faktor lain yang mempengaruhi kejadian diare yaitu kepercayaan dan tradisi dan diharapkan penelitian ini dijadikan sebagai bahan pembanding bagi peneliti selanjutnya. Kata Kunci : Pengetahuan, Penanganan Kegawat Daruratan, Diare